The Effect of Financial Well-Being and Work Facilities on the Productivity of Hybrid Generation Z Workers: The Mediating Role of Work Motivation - Handayani, Melly; Nururly, Santi; Husnan, Lalu Hamdani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of Financial Well-Being and workplace facilities on the productivity of hybrid Generation Z workers, with work motivation serving as a mediating variable. The study employs a quantitative approach using a causal associative research design, and data were analyzed using Structural Equation Modeling (SmartPLS 3.0). The population of this research consists of 2,678,252 individuals based on data from Statistics Indonesia (BPS), while the sample comprises 119 respondents determined using the Slovin formula and selected through a non-probability sampling technique. The findings reveal that Financial Well-Being and workplace facilities have a positive and significant effect on both work motivation and productivity. Work motivation also has a positive and significant effect on productivity. Furthermore, work motivation is proven to mediate the relationship between Financial Well-Being and workplace facilities on productivity. These findings highlight that adequate workplace facilities are the most influential factor in enhancing the productivity of hybrid Generation Z workers.